Event Marketing Female Daily X Beauty dan Brand Loyalty Pengunjung - Aliyyanabila Yuwono; Ratih Pandu Mustikasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to describe the brand loyalty groups among visitors of Female Daily Network after attending the Female Daily X Beauty event marketing campaign. The research is grounded in the increasing significance of event marketing as a strategic communication tool, particularly within the beauty industry. More than just a promotional platform, this event serves as a curated brand experience designed to foster emotional bonds between consumers and the brand. Using the Theory of Consumption Value (TCV) by Sheth, Newman, and Gross (1991), the study explores how functional, emotional, social, epistemic, and conditional values derived from the event influence consumers’ loyalty. A descriptive quantitative method was applied, using a Likert-scale questionnaire distributed to 100 respondents who had previously attended the event. Data analysis was performed by calculating the mean, median, and mode for five brand loyalty indicators based on Aaker’s framework: switcher buyer, habitual buyer, satisfied buyer, liking the brand, and committed buyer. The results show that "liking the brand" had the highest score among respondents, indicating a strong emotional resonance and affinity toward Female Daily Network after the event. These findings suggest that well-executed event marketing can generate deep emotional loyalty, enhancing brand attachment beyond transactional relationships. In conclusion, the study affirms that event marketing, when designed with consumer value dimensions in mind, serves as an effective approach to strengthening long-term consumer-brand relationships. This is especially relevant in today’s experience-driven market where emotional connection plays a central role in influencing brand preference and consumer loyalty.